Evaluating Financial Statement Presentation Compliance and Auditor Opinion Based on BPK-RI Examination: A Case Study in West Java Local Governments - M, Diana; Pruyudo, Bayu; Rukhviyanti, Novi (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2023)
This research aims to analyze the financial accountability of local governments in West Java based on the examination results of the Supreme Audit Agency (BPK-RI) on the Local Government Financial Statements (LKPD), specifically by mapping and analyzing issues related to the fairness of LKPD presentation and compliance with regulations. The study covers all regencies and cities in West Java for the period of LKPD 2018-2019, which were audited by BPK-RI, resulting in 54 research units. This research adopts a descriptive approach with a method of descriptive content analysis to explain the issues of local government financial accountability. The analysis is conducted on qualitative data in the form of texts/sentences that describe the issues in the BPK-RI audit report on LKPD. The findings reveal that the most common issues affecting the auditor's opinion on the fairness of LKPD presentation are non-compliance with Government Accounting Standards (SAP). The compliance issues with regulations that cause the most significant losses to the local government are indications of asset misuse.